2018
DOI: 10.1371/journal.pone.0199710
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing ebselen for decolonization of vancomycin-resistant enterococci (VRE)

Abstract: Enterococci represent one of the microbial world’s most challenging enigmas. Colonization of the gastrointestinal tract (GIT) of high-risk/immunocompromised patients by enterococci exhibiting resistance to vancomycin (VRE) can lead to life-threating infections, including bloodstream infections and endocarditis. Decolonization of VRE from the GIT of high-risk patients represents an alternative method to suppress the risk of the infection. It could be considered as a preventative measure to protect against VRE i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 52 publications
3
44
0
1
Order By: Relevance
“…Drug repositioning is a promising field that investigates new therapeutic opportunities for existing approved drugs with readily available information on their pharmacokinetic profile, dosages, and toxicity to humans (14)(15)(16)(17)(18)(19). This approach can significantly reduce the total cost, time, and effort to develop novel antibacterial agents.…”
mentioning
confidence: 99%
“…Drug repositioning is a promising field that investigates new therapeutic opportunities for existing approved drugs with readily available information on their pharmacokinetic profile, dosages, and toxicity to humans (14)(15)(16)(17)(18)(19). This approach can significantly reduce the total cost, time, and effort to develop novel antibacterial agents.…”
mentioning
confidence: 99%
“…At the outset of this study, the initial antibacterial screening was performed on methicillinresistant Staphylococcus aureus (MRSA, 2658 RCMB). The results presented in Table 1 indicated that the 2-amino-1,3,4oxadiazole linker with aliphatic side chains (compounds [8][9][10][11][12][13][14][15][16][17] is void of anti-MRSA activity.…”
Section: Biological Results and Discussionmentioning
confidence: 99%
“…Against vancomycin-resistant enterococci (VRE), Ebselen exhibited potent bactericidal activity in vitro , and a distinct lack of Ebselen-resistant VRE after prolonged passaging. 81 As with multidrug-resistant staphylococcal biofilms, Ebselen was shown to significantly reduce established VRE biofilms. 81 With the antimicrobial activity demonstrated against other notable pathogens, it becomes an attractive option to explore as an antimicrobial against CD.…”
Section: Small Molecule Inhibitors Of C Difficile Toxinsmentioning
confidence: 99%
“… 81 As with multidrug-resistant staphylococcal biofilms, Ebselen was shown to significantly reduce established VRE biofilms. 81 With the antimicrobial activity demonstrated against other notable pathogens, it becomes an attractive option to explore as an antimicrobial against CD. Work by Bender et al 80 and Beilhartz et al 82 identified and demonstrated the ability of Ebselen to inhibit the activity of CD toxins.…”
Section: Small Molecule Inhibitors Of C Difficile Toxinsmentioning
confidence: 99%